A successful search for intervening 21 cm H i absorption in galaxies at 0.4 < z <1.0 with the Australian square kilometre array pathfinder (ASKAP). Issue 3 (31st August 2020) - Sadler, Elaine M; Moss, Vanessa A; Allison, James R; Mahony, Elizabeth K; Whiting, Matthew T; Johnston, Helen M; Ellison, Sara L; Lagos, Claudia del P; Koribalski, Bärbel S
ABSTRACT: We have used the Australian Square Kilometre Array Pathfinder (ASKAP) radio telescope to search for intervening 21 cm neutral hydrogen (H i ) absorption along the line of sight to 53 bright radio continuum sources. Our observations are sensitive to H i column densities typical of Damped Lyman Alpha absorbers (DLAs) in cool gas with an H i spin temperature below about 300–500 K. The six-dish Boolardy Engineering Test Array (BETA) and twelve-antenna Early Science array (ASKAP-12) covered a frequency range corresponding to redshift 0.4 < z < 1.0 and 0.37 < z < 0.77, respectively, for the H i line. Fifty of the 53 radio sources observed have reliable optical redshifts, giving a total redshift path Δ z = 21.37. This was a spectroscopically untargeted survey, with no prior assumptions about the location of the lines in redshift space. Four intervening H i lines were detected, two of them new. In each case, the estimated H i column density lies above the DLA limit for H i spin temperatures above 50–80 K, and we estimate a DLA number density at redshift z ∼ 0.6 of $n(z)=0.19^{+0.15 }_{ -0.09}$ . This value lies somewhat above the general trend of n ( z ) with redshift seen in optical DLA studies. Although the current sample is small, it represents an important proof of concept for the much larger 21 cm First Large Absorption Survey in H i (FLASH) project to be carried out with the full 36-antenna ASKAP telescope, probing a total redshift path $Δ z\sim \, 50, 000$ .